Potential ecotourism attractions in Sungai Rawog Conservation Area, Segaliud Lokan Forest Reserve, Sabah - J.K. Lajanga; Andy Russel Mojiol; R.A. Rashid (Sabah Forestry Department, 2019)
This paper aims to compile the main findings from a scientific expedition of the Sungai Rawog Conservation Area (SRCA), Segaliud Lokan Forest Reserve, Sandakan, which was conducted from 8th to 18th August, 2018. A fieldwork observation was used to collect the potential attractions of the areas, including the natural landscapes, which can be developed as an ecotourism site. Findings from SWOT analysis identified the strength of flora and fauna biodiversity, as well as the stewardship of conserving the natural resources by the management. Forest encroachment is one of the identified weaknesses that needs regular monitoring systems. Developing the SRCA as an ecotourism site is an opportunity that is beneficial to KTSP, local community and the surrounding areas. On the other hand, threats from human activities and natural disasters can not be eliminated, but proactive measures can reduce the impact.